(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The international field has witnessed economical and technological developments which made the world one market . this increased the competence among the international dealers . the market, thus comprises states, governments, international organizations, and giant economic blocs which all seek to unify the behavior of the game by dealing and seizing the opportunities and facing the threats which concern deregulation in all its forms .This led to a number of developments including the increasing number of mergers and posts which are considered investment alternatives. In the light of changes taking place in Iraq and the extension of what is happening thus foreign banks were allowed to enter Iraq and to contribute together to work with Iraqi private banks in order to develop the Iraqi banking environment and gain experience to keep pace with this development. So this study intends to identify this type of foreign investment in Iraq through the so-called foreign participation in the capital of Iraqi private banks, which is a new experience with these banks and pinpoints the impact of this experience on those banks in improving their performance and achievements dne to the increase in capital and an increase in deposits, profits and an improvement in the quality of services provided and the excellent reputation of the bank co-whether inside or outside Iraq as a result of such participation as well as the possibility of expansion and development of these banks and their ability to face competition from other banks internationally and globally. The research found a number of recommendations to enhance this experience by addressing some of the negatives that accompanied it.